2000
DOI: 10.1006/jabr.1999.7956
|View full text |Cite
|
Sign up to set email alerts
|

Hilbert–Kunz Multiplicity and an Inequality between Multiplicity and Colength

Abstract: In this paper, we study local rings of small Hilbert-Kunz multiplicity. In particular, we prove that an unmixed local ring of Hilbert-Kunz multiplicity one is regular and classify two-dimensional Cohen-Macaulay local rings whose Hilbert-Kunz multiplicity is 2 or less. Also, we investigate the inequality between the multiplicity and the colength of the tight closure of parameter ideals inverse to the usual inequality between multiplicity and colength.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(86 citation statements)
references
References 19 publications
1
85
0
Order By: Relevance
“…In [4] Hanes recently showed that, in fact, e(I)/d! < e HK (I), for every m-primary ideal I, answering affirmatively a question raised by Watanabe and Yoshida (Question 2.9 in [7]). …”
Section: Lower Bounds On the Hilbert-kunz Multiplicitysupporting
confidence: 52%
See 2 more Smart Citations
“…In [4] Hanes recently showed that, in fact, e(I)/d! < e HK (I), for every m-primary ideal I, answering affirmatively a question raised by Watanabe and Yoshida (Question 2.9 in [7]). …”
Section: Lower Bounds On the Hilbert-kunz Multiplicitysupporting
confidence: 52%
“…In the one-dimensional case this is trivial, HK (1) = 1. Work of Watanabe and Yoshida [7], together with our Remark 2.6, shows that HK (2) = 1/2. Furthermore, Watanabe and Yoshida give a classification of all twodimensional Cohen-Macaulay rings with Hilbert-Kunz multiplicity less than 2.…”
Section: Proposed Problemsmentioning
confidence: 65%
See 1 more Smart Citation
“…(Fundamental properties (cf. [13], [15], [16], [18], [22])) Let (A, m, k) be a local ring of positive characteristic. Let I, I be m-primary ideals of A, and let M be a finitely generated A-module.…”
Section: Introductionmentioning
confidence: 99%
“…They can be found in [WY,Proposition 4.1,Lemma 4.2] in slightly different forms. The filtration argument used in the proof can also be found in [Ha,Proposition 5.2.1].…”
Section: Preliminariesmentioning
confidence: 99%